Differential expression of Arabidopsis sulfurtransferases under various growth conditions - Bartels, Andrea (Plant physiology and biochemistry : PPB, 2007)
Sulfurtransferases (Str) comprise a group of enzymes widely distributed in archaea, eubacteria, and eukaryota which catalyse the transfer of a sulfur atom from suitable sulfur donors to nucleophilic sulfur acceptors. Neither the in vivo sulfur donors nor the acceptors of Str could be clearly identified in any of the organisms investigated so far. In Arabidopsis thaliana 20 Str proteins have been identified and grouped according to sequence homology. To investigate their respective in vivo function, Arabidopsis plants were grown in sterile hydroponic cultures at different sulfate (50, 500, and 1500 microM) and phosphate (0.1 and 1mM) concentrations, and in medium supplemented with 1mM thiosulfate. Northern blot analysis revealed the differential expression of the Str investigated. Thiosulfate Str activity was significantly increased at low sulfate concentrations in the medium. The Str mRNA levels were highly dependent on the developmental stage of the Arabidopsis plants. The expression of most Str analysed increased with progressing plant age in parallel with increasing 3-mercaptopyruvate and thiosulfate Str activities. The Str investigated were differentially expressed in a light/dark cycle whereas Str enzyme activities were not affected by the light conditions. The results indicate that each Str is regulated in a different way and plays an individual specific role in the plant metabolism